Navigating Passports and Borders: The Complex Realities of Zimbabwean Migrants in South Africa - Chekero, Tamuka; Bhanye, Johannes; Mushonga, Rufaro Hamish; Nyamwanza, Owen (African Human Mobility Review, 2025)
The acquisition and maintenance of valid passports present complex challenges for many migrants. The complexity arises from many factors including political, economic, and administrative. Employing a multi-sited ethnographic approach, this study scrutinizes the hurdles encountered by Zimbabwean migrants in South Africa when obtaining and renewing passports, visas, and permits. Moreover, the study investigates the far-reaching repercussions of passport-related complexities on the daily existence and welfare of these migrants. The socio-political dynamics shaping the passport experiences of Zimbabwean migrants offer valuable insights into fostering more inclusive migration policies and procedures. Consequently, these challenges significantly impact migrants’ daily lives and overall well-being, impeding their pursuit of a better life in South Africa. In response, migrants resort to “nimble-footed strategies,” such as using ephemeral stamps, to navigate their circumstances. However, these strategies also leave migrants vulnerable to exploitation and a lack of state protection. In essence, this study contributes to understanding the contemporary challenges faced by migrants amidst evolving global crises, particularly in the post-COVID-19 era marked by increased regulation and restriction of migrants. This study traverses diverse geographical and political contexts, by shedding light on the ongoing militarization and contraction of borders and the rights of migrants.